Digestion of animal- and plant-based proteins encapsulated in κ-carrageenan/protein beads under simulated gastrointestinal conditions. (November 2020) - Ozel, Baris; Zhang, Zhiyun; He, Lili; McClements, David Julian
Graphical abstract: Highlights: Protein/polysaccharide beads were fabricated from plant and animal proteins. All beads were digested slowly in the stomach but rapidly in the small intestine. Raman spectroscopy was used to analyze beads during gastrointestinal digestion. Similar digestion behaviors were observed for whey, soy and pea protein beads. Animal proteins can be replaced by plant ones in hydrogel delivery systems. Abstract: In this study, we encapsulated both animal-derived (whey) and plant-derived (soy and pea) proteins within polysaccharide/protein beads and measured the digestion of these beads under simulated gastrointestinal tract (GIT) conditions. Bead dimensions were measured using a digital caliper and found to increase as the shear thinning behavior of the protein/polysaccharide solutions used to form them increased. The hydrolysis of the plant and animal proteins trapped inside the protein/polysaccharide beads was studied using the pH-stat automatic titration method under simulated static GIT conditions. The encapsulated proteins were relatively resistant to digestion under gastric conditions, with only about 10 to 13% of the protein being digested by the end of the stomach phase. Conversely, they were almost fully digested under small intestinal conditions, with around 87 to 97% of the protein being hydrolyzed by the end. Indeed, by the completion of the small intestine phase, only "ghost" beads remained that contained cross-linked polysaccharides. The soy and pea proteins were digested slightly faster than the whey proteins in the stomach phase ( p < 0.05), whereas the pea proteins were digested slightly faster than the soy and whey proteins under intestinal conditions ( p < 0.05). Raman spectroscopy and scanning electron microscopy showed that there were changes in the composition and structure of the beads throughout the simulated GIT. Our results indicate that the gastrointestinal behavior of proteins can be modulated by encapsulating them in polysaccharide beads, which may be useful for the design of certain types of functional foods. Even so, the beads formed from the plant-based and animal-based proteins behaved fairly similarly, suggesting that animal proteins could be replaced by plant-based ones for this purpose.